Evaluasi Aplikasi Sistem Akuntansi Instansi Berbasis Akrual Pada Dinas Kehutanan Provinsi Jawa Barat - Syifa Fadhilatunnisa; Ai Siti Farida (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
This study aims to evaluate the implementation of the Accrual Based Agency Accounting System at the West Java Province Forestry Service in 2016-2019 as an implementation of the Accrual Based Government Accounting Standards. Evaluation of SAIBA applications used includes: Technical Feasibility, Operational Feasibility and Economic Feasibility are the theories of Bambang Hartono (2013). Descriptive qualitative research methods, data collection techniques with observation, documentation, interviews, and triangulation, and data analysis techniques using Miles and Huberman model analysis consisting of (1) data reduction, (2) data presentation, and (3) drawing conclusions/verification.Based on the results of the study that the results of the analysis showed an evaluation of the application of the Accrual Based Institution Accounting System (SAIBA) in the West Java Provincial Forestry Work Unit based on the evaluation of the Management Information System (SIM) application, (1) the technical feasibility of the SAIBA application measured in two indicators namely easy technology and low-cost technology shows that the SAIBA application has been quite successful, (2) the operational feasibility of the SAIBA application related to the evaluation of the SIM application has been running quite well when viewed in terms of timely reporting and accepted by the KPPN, but there are other things related to the output indicators are successful namely regarding the budget realization report, which before using the SAIBA report reached the target of 100%, but after using SAIBA there was a decrease in the achievement of the target which was between 70-90%, (3) economic feasibility, where costs and benefits were comparable.